Re-dating Alcuin's De dialectica: or, did Alcuin teach at Lorsch?. (24th July 2017) - Rädler-Bohn, Eva M. E.
Abstract: Alcuin's De dialectica has traditionally been dated to Alcuin's second stay at Charlemagne's court ( c . 795–6/7). This dating has been based on the perceived dating for another didactic work by Alcuin, De rhetorica . It will be argued that De dialectica (and De rhetorica ) must be dated to Alcuin's first period on the Continent ( c . 784/6–90). The new dating is primarily based on a philological comparison between De dialectica and Opus Caroli regis (written 790–3 by Theodulf of Orleans) but appears to be confirmed both by the contents of De dialectica and by its use of specific sources. In dating De dialectica to Alcuin's first stay on the Continent, we must now also reassess Alcuin's work as presenting a unique testimony to the scholarly structures and intellectual initiatives of the otherwise badly attested pre-Aachen phase of Charlemagne's court.